Найди значение выражения при d=−0,11,
предварительно упростив его: (d−9)⋅(d+3)−(d+5)⋅(d−15).

cherepd2005 cherepd2005    3   16.01.2021 20:00    0

Ответы
nkarlikova nkarlikova  16.01.2021 20:10

(d-9)(d+3)-(d+5)(d-13) = d²+3d-9d-27-(d²-13d+5d-65)=d²-6d-27-(d²-8d-52)=d²-6d-27-d²+8d+52=2d+38=-0,38+38=37,62

Объяснение:

ПОКАЗАТЬ ОТВЕТЫ
lenok140 lenok140  16.01.2021 20:10

(d²+3d-9d-27) - (d²-15d+5d-75) = d²+3d-9d-27 -d²+15d-5d+75=4d+48

4*(-0.11) +48= -0.44 +48= 47.56

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра